A Treatment-as-Prevention Trial to Eliminate Hepatitis C Among Men Who Have Sex With Men Living With Human Immunodeficiency Virus (HIV) in the Swiss HIV Cohort Study. (6th August 2020) - Braun, Dominique L; Hampel, Benjamin; Ledergerber, Bruno; Grube, Christina; Nguyen, Huyen; Künzler-Heule, Patrizia; Shah, Cyril; Salazar-Vizcaya, Luisa; Conen, Anna; Flepp, Markus; Stöckle, Marcel; Béguelin, Charles; et al.
Abstract: Background: In 2016, the World Health Organization (WHO) introduced global targets for the elimination of hepatitis C virus (HCV) by 2030. We conducted a nationwide HCV micro-elimination program among men who have sex with men (MSM) living with human immunodeficiency virus (HIV) from the Swiss HIV Cohort Study (SHCS) to test whether the WHO goals are achievable in this population. Methods: During phase A (10/2015–06/2016), we performed a population-based and systematic screening for HCV-RNA among MSM from the SHCS. During phase B (06/2016–02/2017) we offered treatment with HCV direct-acting antiviral (DAA) agents to MSM identified with a replicating HCV infection. During phase C (03/2017–11/2017), we offered rescreening to all MSM for HCV-RNA and initiated DAA treatment in MSM with replicating infections. Results: We screened 3715/4640 (80%) MSM and identified 177 with replicating HCV infections (4.8%); 150 (85%) of whom started DAA treatment and 149 (99.3%) were cured. We rescreened 2930/3538 (83%) MSM with a prior negative HCV-RNA and identified 13 (0.4%) with a new HCV infection. At the end of the micro-elimination program, 176/190 MSM (93%) were cured, and the HCV incidence rate declined from .53 per 100 patient-years (95% CI, .35–.83) prior to the intervention to .12 (95% CI, .03–.49) by the end of 2019. Conclusions: A systematic, population-based HCV micro-elimination program among MSM living with HIV was feasible and resulted in a strong decline in HCV incidence and prevalence. Our study can serve as a model for other countries aiming to achieve the WHO HCV elimination targets. Clinical Trials Registration: NCT02785666. Abstract : We systematically assessed the feasibility of a test, treat, and cure hepatitis C virus (HCV) micro-elimination program among men who have sex with men living with human immunodeficiency virus. Our elimination program led to a 77% decrease in the HCV incidence rate.